Video Edukasi sebagai Intervensi untuk Mengurangi Prokrastinasi Akademik di Sekolah: Sebuah Eksperimen - Maghfirotul Lathifah; Muhammad Septerino; Nawang Khairunisa Putri (Lembaga Pengembangan Kinerja Dosen, 2025)
This research is motivated by the high level of academic procrastination found among students, particularly related to the habit of postponing assignments or homework. Persistent academic procrastination can negatively impact academic achievement, learning discipline, and character development. Therefore, this study aims to determine the effectiveness of using educational videos in reducing academic procrastination among students at MAN 1 Gresik in the 2023–2024 academic year. This study used a quantitative approach with a one-group pre-test-post-test pre-experimental design. The research instrument used a Likert scale to measure procrastination levels before and after the intervention. Information services through educational videos were provided in the form of a group guidance program designed to increase students' understanding of the impact of procrastination and motivate them to be more disciplined in managing their study time. The results showed that the use of educational videos was effective in reducing academic procrastination, as evidenced by lower post-test scores compared to pre-test scores.